Thermal and solutal analysis of local thermal non-equilibrium effects on gyrotactic microbes in radiative flow of hybrid nanofluid with Soret–Dufour effects - Munawar Abbas; Mostafa Mohamed Okasha; Tatyana Orlova; Ali Akgül; Murad Khan Hassani; Saba Liaqat (International Journal of Thermofluids, 2025)
The present research investigates the impact of local thermal non-equilibrium on radiative flow of a hybrid nanofluid around a revolving sphere in the presence of gyrotactic microbes and porous medium. To explore heat transfer characteristics in cases where LTE (local thermal equilibrium) is not assumed, the research provides use of a basic mathematical model. In LTNE conditions, the solid and liquid phases experience distinct thermal gradients. SWCNTs (Single-walled carbon nanotubes) and MWCNTs (multi-walled carbon nanotubes) suspended in water make up the hybrid nanofluid under discussion. In order to compare the modified model's heat transfer performance with that of the conventional Hamilton-Crosser model, this study specifically concentrate at the hybrid nanofluid that consists of MWCNTs, SWCNTs, and water. To convert the constitutive equations into ODEs, similarity variables were used. and MATLAB's Bvp4c function has been employed to find solutions. The results suggest that relative to the modified model, classical model can predict increased heat transmission rates with adequate precision. The findings improve the precision of models for thermal conductivity and advance our considerate of the properties of hybrid nanofluid heat transfer. The solid-phase thermal field and the liquid-phase thermal transmission rate both decrease with increasing interphase heat transfer factor in both the modified and classical Hamilton–Crosser models.